2014
DOI: 10.1016/j.exer.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to glaucoma damage related to age and connective tissue mutations in mice

Abstract: The purpose of this research was to study the effects of age and genetic alterations in key connective tissue proteins on susceptibility to experimental glaucoma in mice. We used mice haploinsufficient in the elastin gene (EH) and mice without both alleles of the fibromodulin gene (FM KO) and their wild type (WT) littermates of B6 and CD1 strains, respectively. FM KO mice were tested at two ages: 2 months and 12 months. Intraocular pressure (IOP) was measured by Tonolab tonometer, axial lengths and widths meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In addition, certain conditions, such as advancing age, can make ganglion cells more susceptible to death when exposed to the same pressure rise in some models (Kim et al, 2004; Steinhart et al, 2014). Understanding the endogenous mechanisms that minimize the pathological effects of increased mechanical strain on the neurons is a key target in preventing their loss in disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, certain conditions, such as advancing age, can make ganglion cells more susceptible to death when exposed to the same pressure rise in some models (Kim et al, 2004; Steinhart et al, 2014). Understanding the endogenous mechanisms that minimize the pathological effects of increased mechanical strain on the neurons is a key target in preventing their loss in disease.…”
Section: Discussionmentioning
confidence: 99%
“…IOP spikes should therefore be higher in the elderly, and even higher in persons of African descent, which may contribute to the increased glaucoma prevalence in these at risk populations. Recent work in an experimental mouse model of glaucoma supports this view, in that a stiffer sclera was associated with increased ganglion cell loss (Nguyen, Cone et al 2013, Pease, Oglesby et al 2014, Steinhart, Cone-Kimball et al 2014). Also, Vande Geest and coworkers observed that the local orientation of the collagen fibrils changes through the thickness of the sclera and was found to be different between donors of African heritage versus European heritage, although no significant changes were seen with age (Yan, McPheeters et al 2011).…”
Section: Remodeling Of the Optic Nerve Head With Age And Diseasementioning
confidence: 92%
“…We have recently found that older CD1 mice are more susceptible to experimental glaucoma damage than younger CD1 mice. 42 Older CD1 mice have also longer eyes, which might logically lead to increased strain in the sclera, all other factors being equal. Yet, lower scleral permeability was associated here with those mouse strains less susceptible to glaucoma.…”
Section: Discussionmentioning
confidence: 99%